Impact of maternal diabetes mellitus on mortality and morbidity of very low birth weight infants: a multicenter Latin America study - Carlos Grandi; Jose L. Tapia; Viviane C. Cardoso (Elsevier, 2015)
OBJECTIVES: To compare mortality and morbidity in very low birth weight infants (VLBWI) born to women with and without diabetes mellitus (DM). METHODS: This was a cohort study with retrospective data collection (2001-2010, n = 11.991) from the NEOCOSUR network. Adjusted odds ratios and 95% confidence intervals were calculated for the outcome of neonatal mortality and morbidity as a function of maternal DM. Women with no DM served as the reference group. RESULTS: The rate of maternal DM was 2.8% (95% CI: 2.5-3.1), but a significant (p = 0.019) increase was observed between 2001-2005 (2.4%, 2.1-2.8) and 2006-2010 (3.2%, 2.8-3.6). Mothers with DM were more likely to have received a complete course of prenatal steroids than those without DM. Infants of diabetic mothers had a slightly higher gestational age and birth weight than infants of born to non-DM mothers. Distribution of mean birth weight Z-scores, small for gestational age status, and Apgar scores were similar. There were no significant differences between the two groups regarding respiratory distress syndrome, bronchopulmonary dysplasia, intraventricular hemorrhage, periventricular leukomalacia, and patent ductus arteriosus. Delivery room mortality, total mortality, need for mechanical ventilation, and early-onset sepsis rates were significantly lower in the diabetic group, whereas necrotizing enterocolitis (NEC) was significantly higher in infants born to DM mothers. In the logistic regression analysis, NEC grades 2-3 was the only condition independently associated with DM (adjusted OR: 1.65 [95% CI: 1.2 -2.27]). CONCLUSIONS: VLBWI born to DM mothers do not appear to be at an excess risk of mortality or early morbidity, except for NEC.